KOTOWAZA DALAM KAJIAN LINGUISTIK KOGNITIF: PENERAPAN GAYA BAHASA SINEKDOK - Yohani, Adisthi Martha (Universitas Diponegoro, 2016)
[Kotowaza in Cognitive Linguistic Analysis: The Use of Synecdoche]. This paper analyzes kotowaza using synecdoc through the study of cognitive linguistic. The background of this research is the difficulty of understanding relationships between the meanings of the kotowaza on foreign learners because of cultural differences and lack of dictionaries that support the process of understanding kotowaza deeply. The purpose of this research is to understand kotowaza deeply, determine the connection of these lexical-figurative meaning of Japanese proverbs using synecdoche based on the study of cognitive linguistics. The method used is a qualitative method in approach of cognitive linguistics. At the end of the study, it is concluded that synecdochecan be used to analyze the correlation between the lexical meaning and figurative meaning of kotowaza that contains a word or two which represents wider or smaller meaning such as kotowaza which related to the characteristics of an area or kotowaza that associated with number. <a href=